Hospital Variation in Maternal Complications Following Caesarean Delivery in the United States: 2006 to 2012. Issue 1 (March 2017) - Moroz, L.A.; Wright, J.D.; Ananth, C.V.; Friedman, A.M.
Abstract : ( BJOG. 2016;123:1115–1120) Caesarean delivery (CD) is associated with postsurgery complications such as wound infections, hemorrhage, and organ injury, and is one factor associated with increased maternal morbidity. Earlier studies have demonstrated the role of hospital factors and obstetric factors in patient outcomes. This study aimed to evaluate patient, obstetric, and hospital-related factors associated with post-CD complications, and hypothesized that hospital variability may be a useful parameter to assess quality of care and ultimately serve as a target for implementing interventions with the goal of improving patient outcomes.